Redistribution of CHH Methylation and Small Interfering RNAs across the Genome of Tomato ddm1 Mutants. Issue 7 (6th June 2018) - Corem, Shira; Doron-Faigenboim, Adi; Jouffroy, Ophélie; Maumus, Florian; Arazi, Tzahi; Bouché, Nicolas
Abstract : The production of siRNAs and the CHH methylation mediated by the RdDM pathway are enhanced in heterochromatin when DDM1 is nonfunctional, at the expense of silencing mechanisms occurring in euchromatin. Abstract: In plants, cytosine methylation, an epigenetic mark critical for transposon silencing, is maintained over generations by key enzymes that directly methylate DNA and is facilitated by chromatin remodelers, like DECREASE IN DNA METHYLATION1 (DDM1). Short-interfering RNAs (siRNAs) also mediate transposon DNA methylation through a process called RNA-directed DNA methylation (RdDM). In tomato ( Solanum lycopersicum ), siRNAs are primarily mapped to gene-rich chromosome arms, and not to pericentromeric regions as in Arabidopsis thaliana . Tomato encodes two DDM1 genes. To better understand their functions and interaction with the RdDM pathway, we targeted the corresponding genes via the CRISPR/Cas9 technology, resulting in the isolation of Slddm1a and Slddm1b knockout mutants. Unlike the single mutants, Slddm1a Slddm1b double mutant plants display pleiotropic vegetative and reproductive phenotypes, associated with severe hypomethylation of the heterochromatic transposons in both the CG and CHG methylation contexts. The methylation in the CHH context increased for some heterochromatic transposons and conversely decreased for others localized in euchromatin. We found that the number of heterochromatin-associated siRNAs, including RdDM-specific small RNAs, increased significantly, likely limiting the transcriptional reactivation of transposons in Slddm1a Slddm1b . Taken together, we propose that the global production of siRNAs and the CHH methylation mediated by the RdDM pathway are restricted to chromosome arms in tomato. Our data suggest that both pathways are greatly enhanced in heterochromatin when DDM1 functions are lost, at the expense of silencing mechanisms normally occurring in euchromatin.